A review on designing nanofibers with high porous and rough surface via electrospinning technology for rapid detection of food quality and safety attributes. (October 2022) - Hajikhani, Mehdi; Lin, Mengshi
Abstract: Background: Agricultural and food products are highly perishable, which require advanced detection methods to monitor their quality. Electrospinning technology is a novel fiber production technique using electric force to draw charged threads of polymer solutions, leading to the elongation and thinning of the fiber and forming uniform fibers with nanometer-scale diameters. Electrospun nanofibers have unique surface properties such as high specific surface area and porosity, which can increase their potential for use as sensors for rapid detection with high accuracy and sensitivity. Scope and approach: This review summarizes recent advances in using electrospinning technology to synthesize nanofibers with high porous and rough surfaces. The nanofibers can be used in rapid sensing methods to monitor food quality and safety attributes, including contaminants such as pesticide residues. The morphological control of electrospun nanofibers to increase the resolution of rapid detection sensors was discussed. Some recent achievements in identifying different analytes using electrospinning technology are elaborated, including SERS, aptamer-based biosensors, surface plasmon resonance sensors, and the direct electron transfer method. Key findings and conclusions: Electrospinning technology can be used to control the surface properties of nanofibers to design sensors and substrates for the rapid detection of various contaminants. Recent studies showed an improvement in the performance of sensors, such as higher accuracy, a lower limit of detection, and higher resolution due to the use of electrospun scaffolds in the design of sensors. The combination of electrospinning technology with sensors has great potential for applications in the food industry. Highlights: Electrospinning concept is reviewed from the perspective of sensing systems. A detailed guidance and workflow are elucidated based on designing high-porous electrospun nanofibers. The use of electrospun structures in sensors significantly increases the speed, accuracy, and efficiency of sensors. Electrospinning applications are summarized from the perspective of different classifications of sensor techniques.